The Black Heralds: Relations and Frictions with the Aesthetics of their Time - Pantigoso Pecero, Manuel Trinidad (2020)
This article begins placing The Black Heralds in the social, political and literary context of the time, pointing out their relations as well as their differences with the still current Hispanic American modernism and with the avant-garde, as well as their condition of «libro puente» [«bridge word»] agglutinative of themes that will be reiterated and expanded in the maturity of their future work, such as pain, human piety, indigenous feeling, home, love, eroticism, social drama, eternity; all of them thematic focus by which Peruvian poetry will be oriented.